Tendon Multiscale Structure, Mechanics, and Damage Are Affected by Osmolarity of Bath Solution - Bloom, Ellen T (Ann Biomed Eng, 2020)
One of the most common bath solutions musculoskeletal mechanical testing is phosphate buffered saline (PBS). In tendon, swelling induced by physiological PBS results in decreased tendon modulus and induces microstructural changes. It is critical to evaluate the multiscale mechanical behavior of tendon under swelling to interpret prior work and provide information to design future studies. We compared the effects of physiological PBS and 8% SPEG bathing solutions on tendon multiscale tendon mechanics and damage as well as microstructure with TEM in order to understand the effect of swelling on tendon. At the tissue level, tendons in PBS had a lower modulus than SPEG samples. PBS samples also showed an increased amount of non-recoverable sliding, which is an analog for microscale damage. SPEG had a higher microscale to tissue-scale strain ratio, showing the fibrils experienced less strain attenuation. From the TEM data, we showed the fibril spacing of SPEG samples was more similar to fresh control than PBS. We concluded that swelling alters multiscale mechanics and damage in addition to tendon microstructure. Future mechanical testing should consider using SPEG as a bath solution with an osmotic pressure which preserves fresh tissue water content.